2019
DOI: 10.1332/174426417x15139342679329
|View full text |Cite
|
Sign up to set email alerts
|

Policy networks revisited: creating a researcher–policymaker community

Abstract: The need for better linkages between evidence and policymaking has been well established in the literature, with a heightened focus on the relationship between researchers, research utilisation and policy development. However, fostering such linkages using a policy network approach has seldom been discussed. This article revisits a key framework in the policy network literature: the policy community, to shed further light on such linkages. Using an empirical approach built on the experience of the Social Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Resilience within, and between, networks as a response to EU policy processes is implicit within this work but no explicit conceptual framework has been developed in this field. This is surprising given that resilience and adaptability are key criteria for judging the success of policy networks (Agranoff and McGuire, 2001; Bevir and Richards, 2009; Ranchod and Vas, 2019). Bakker et al (2012) provide an overview of the definitions of resilient networks and conclude that the most common elements of the definitions are the ability of networks to remain operational in the midst of perturbations or shocks and have ‘rebounding capacities’ in the face of exogenous change.…”
Section: Understanding Network Resilience In Third Countriesmentioning
confidence: 99%
“…Resilience within, and between, networks as a response to EU policy processes is implicit within this work but no explicit conceptual framework has been developed in this field. This is surprising given that resilience and adaptability are key criteria for judging the success of policy networks (Agranoff and McGuire, 2001; Bevir and Richards, 2009; Ranchod and Vas, 2019). Bakker et al (2012) provide an overview of the definitions of resilient networks and conclude that the most common elements of the definitions are the ability of networks to remain operational in the midst of perturbations or shocks and have ‘rebounding capacities’ in the face of exogenous change.…”
Section: Understanding Network Resilience In Third Countriesmentioning
confidence: 99%
“…National policymakers are sometimes described in policy research as important stakeholders who are hard to reach. For example, researchers have discussed how to access (Beyers & Braun, 2014) or how to collaborate with policymakers (Ranchod & Vas, 2019). Nevertheless, here, I explored the stated views of text producing policymakers engaged in the digitalisation of school policies.…”
Section: Conceptualising the Policy Processmentioning
confidence: 99%
“…2. Reasons for -and human labour involved in -creating networks: There is evidence that initiatives aiming to create communities and ties between academics and policymakers help support evidence-informed policymaking (Cooper, 2014;Traynor, Dobbins and DeCorby, 2015;Ranchod and Vas, 2018). However, policymakers draw on broader forms of evidence and expertise, and this diversity must be reflected in future research agendas (as identified in Oliver et al 2016).…”
Section: Use Network Approaches To Optimise Evidence Use Interventionsmentioning
confidence: 99%
“…Certain researchers use the word network as a heuristic or metaphor to describe a (relatively recent) organising principle or social architecture that is assumed to be more agile and less formal than a hierarchy of states or markets (Finnemore, 1996;Parker, 2007;Slaughter and Hale, 2004. Networks are also described as a means to bring policy and evidence communities together by creating links between individuals and organisations (Cooper, 2014;Ward, 2017;Ranchod and Vas, 2018) -still using network as a metaphor, rather than an analytical concept.…”
mentioning
confidence: 99%